PENERAPAN METODE ISTINBATH HUKUM PADA MASALAH KAFA'AH DALAM PERNIKAHAN - adrianto; Haslinda, Haslinda (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2025)
This study aims to describe Increasing how father as a wali of biology for marriage. in the matter of guardianship as nikah often becomes polemic in various cases of marriage especially those involving the biological father not legally recorded the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first, legal status child born out of wedlock in indonesia regulated in the Marriage Law and Islamic Law and is further strengthened by the decision of the Constitutional Court Generally, an illegitimate child only has a civil relationship with their mother and her mother's family However, the verdict of Constitutional Court affirming that the child continues to have a civil relationship with their biological father if it can be scientifically and legally proven The second, The biological father must comply children's rights, such as the right to education right to obtain identity and the right to protection